Designing an app for home-based enriched Music-supported Therapy in the rehabilitation of patients with chronic stroke: a pilot feasibility study. (10th November 2021) - Segura, Emma; Grau-Sánchez, Jennifer; Sanchez-Pinsach, David; De la Cruz, Myriam; Duarte, Esther; Arcos, Josep Lluis; Rodríguez-Fornells, Antoni
ABSTRACT: Objective: After completing formal stroke rehabilitation programs, most patients do not achieve full upper limb motor function recovery. Music-supported Therapy (MST) can improve motor functionality post stroke through musical training. We designed a home-based enriched Music-supported Therapy (eMST) program to provide patients with chronic stroke the opportunity of continuing rehabilitation by themselves. We developed an app to conduct the eMST sessions at home with a MIDI-piano and percussion instruments. Here, we tested the feasibility of the eMST intervention using the novel app. Method: This is a pilot study where five patients with chronic stroke underwent a 10-week intervention of 3 sessions per week. Patients answered feasibility questionnaires throughout the intervention to modify aspects of the rehabilitation program and the app according to their feedback. Upper limb motor functions were evaluated pre- and post-intervention as well as speed and force tapping during daily piano performance. Results: Patients clinically improved in upper limb motor function achieving the Minimal Detectable Change (MDC) or Minimal Clinically Important Difference (MCID) in most of motor tests. The app received high usability ratings post-intervention. Conclusion: The eMST program is a feasible intervention for patients with chronic stroke and its efficacy should be assessed in a clinical trial.